Combining hens for egg production and trees for wood chips in an agroforestry system: lessons learnt after 3 years - Spangenberg, G. (2014)
A 7.1 ha agroforestry field experiment located in south-western Germany demonstrates, how to combine short rotation coppicing for fuel wood production with poultry keeping with the production of eggs. This combined system offers additional ecosystem services and gives multifarious benefits. The agroforestry system has been established since 2009 by an organic farmer (certified) in close cooperation with the University of Applied Forest Sciences Rottenburg. While changing from indoor to outdoor housing required by the standards of organic farming the owner of the farmland wanted to meet not only with the standards, but additionally he wanted to fulfill objectives like: * Raising and keeping hens in a close-to–nature environment, * Finding a way, that hens exploit all the terrain available and not only those areas close to the chicken-coop, * Improving the conditions of the vegetation, soil and hygiene of the hens. The agroforestry system has been implemented based on two components: The first component consists of the construction of mobile chicken-coops (patent of the farmer). The mobile coops can be moved in their position over the experimental plots several times per year without much effort. The second component consists of strips of willows and poplars, which are managed by short rotation coppicing. Trees are harvested every 4 to 7 years and will be marketed as woodchips for energy production. The rootstocks will sprout again after harvesting. The trees offer several additional services in the agroforestry system: * Protection of the hens against hawks, sun and wind (animal health and survival) * Production of renewable resources (renewable energy) * Absorption of nitrogen from the excrements (nutrient cycling in the ecosystem) * Field integration into the country side (aesthetics and landscape planning) The whole experimental field was subdivided into 18 tracts of 0.4 ha. Strips of willow and poplar trees have been established along the tracts. Between the tree strips there is enough space for moving the mobile chicken-coops. Every chicken-coop offers space for 1000 – 1200 hens. In total six coops are installed on the experimental field. The establishment of the trees and the selection of appropriate tree species and provenances have been difficult due to challenging site conditions and standards of organic farming: shallow soil depths, a high clay content and the prohibition of herbicides. Different techniques of non-herbicide-establishment of the short rotation coppicing system have been tested during the last years. For instance the use of mulch foil has emerged as the essential factor for a successful establishment and reduced mortality of trees under such difficult soil conditions. Willows and poplars helped quickly to create a structured field already after two years setting up the agroforestry experiment. In addition the hens indeed use the whole area for grazing and pawing. However the main aim of the adding trees to poultry keeping for egg production is not raising the financial yield with the fuel wood production, but the keeping of the hens in a close-to-nature environment.